Earnings management and managerial compensation in Nigerian manufacturing firms - Okubokeme Derek Opudu; Gbalam Peter Eze (Accounting, 2022)
The growing convolution of industries and the need for corporate business survival has created a cognizance dilemma on the nexus of earnings management and managerial compensation paradigm, especially in developing nations. Hence, this paper sought to examine the nexus of earnings management and managerial compensation in Nigerian manufacturing firms. The study collected panel data from audited annual financial reports of six selected manufacturing firms listed in the Nigeria Stock Exchange, covering the period from, 2012-2019. The data were analyzed using descriptive statistics, correlation and Panel Regression Model. The findings indicate that earnings management is a significant determinant of managerial remuneration. Therefore, the study concludes that managing earnings of firms has a positive significant relationship with executive remuneration, and as such compensation should be tied to performance of the firm in real values.